INVENTARISASI FONEM BAHASA SERAM TIMUR DI MANOKWARI, PAPUA BARAT - Paradida, Yulia Putri; Warami, Hugo; Ansiska, Paisal (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
This research aims to describe the inventory and distribution of phonemes in the East Seram language in Manokwari, West Papua. The data consists of 850 Swadesh core vocabularies obtained in the East Seram language from people from Seram Island who now live in Manokwari. Data sources were obtained from informants' responses or answers to questions asked by researchers both orally and in writing and summarized in a Swadesh list. The method used is descriptive qualitative. Data was collected in depth through direct interaction with informant subjects through observation, interviews, and audio recordings. The process of analyzing the data encompasses transcribing the data, creating a phoneme inventory, and categorizing sounds according to different features, such as articulation and distribution, to recognize vowel and consonant phonemes in the language of East Seram in Manokwari, West Papua. This process includes analyzing phoneme usage patterns in words in initial, middle, and final positions. The results of the data analysis concluded that the East Seram language in Manokwari, West Papua, has 23 segmental phonemes consisting of 18 consonants and five vowels (monophthongs). These phonemes are: p/, /b/, /t/, /d/, /c/, /j/, /k/, /g/, /f/, /s/, /h/, /m/, /n/, /ŋ/, /r/, /l/, /w/, /y/, a/, /i/, /u/, /e/ and /o/.